Public relations theory : application and understanding - Brunner, Brigitta R (Wiley Blackwell, 2019)
"The comprehensive guide to applied PR theory in the 21st century Public Relations Theory explores the central principles and theoretical components of public relations and their practical applications in actual situations. This informative text helps readers to understand the concepts, approaches, and perspectives of PR theory and learn development methods, implementation strategies, management techniques, and more. Chapters written by recognized experts on each topic provide readers with knowledge on how, when, and why appropriate theories are applied. Focusing on how organizations and individuals integrate theory in a public relations framework, each chapter explains one function, explores its potential challenges and opportunities, provides an example of the function in practice, and offers discussion questions and additional reading suggestions.  Unique in structure, this text arranges chapters by function, rather than theory, allowing readers to see how multiple theories can be applied to each public relations function and how theories can be used in different professional settings. Comprehensive treatment of topics including social and emerging media, globalization, public diplomacy, corporate and investor relations, and others ensures relevant and timely coverage of contemporary PR issues. Demonstrates how public relations theory is applied in real-world practice Illustrates how successfully applied public relations theories lead to positive outcomes Discusses the relevance of public relations with accessible and engaging language Offers multiple perspectives from leading international public relations scholars Includes pedagogical tools including chapter discussion questions, practical examples, tables, and suggested reading lists Public Relations Theory: Application and Understanding is suitable for instructors and graduate and advanced undergraduate students in courses on public relations theory, as well as practitioners seeking further knowledge on the most current developments in the field. "--